An electronic neuromorphic system for real-time detection of high frequency oscillations (HFO) in intracranial EEG - Mohammadali Sharifshazileh (Nature Portfolio, 2021)
A major challenge across a variety of fields is how to process the vast quantities of data produced by sensors without large computation resources. Here, the authors present a neuromorphic chip which can detect a relevant signature of epileptogenic tissue from intracranial recordings in patients.